THE HEROIC FEMALE CHARACTER IN FAIRY TALES AND EPICS OF SOME ETHNIC MINORITIES IN THE CENTRAL HIGHLANDS - Thi Tham Dam (Tạp chí Khoa học Đại học Đà Lạt)
The author uses analysis, synthesis, and comparison methods to give readers a comprehensive view of the heroic female character in fairy tales and epics of some ethnic minorities in the Central Highlands. It is an exciting and unique topic since the female hero has not been paid much attention and is rarely mentioned in research papers. Therefore, in this article, the writer has made significant contributions and new findings of the brave female heroes in fairy tales and epics of the Central Highlands. Their talents, wisdom, dignity, and extraordinary health are united. They won battles against sinister villains to protect the peace, prestige, and honor of their villages and themselves when those are violated, which is similar to male heroes. In particular, the heroic female character represents the matriarchy’s authority and the village’s wish for wealth and happiness. Through the image of the heroine, readers will understand more about the regional culture, including customs, habits, lessons about humanity, and beautiful features in the beliefs of ethnic minorities in the Central Highlands.